Design of high frequency antenna - Yang, Quan Bao (2014)
This final year project was to design and develop an Omni-directional antenna that is able to receive and transmit signals which are in frequency range from 2MHz to 30MHz. This antenna was to be placed at most 1 metre above the rooftop of a 19 metre tall building. In addition, the radiation angle should be as close to the horizontal axis of the antenna as possible. This was a challenging project due to the many restrictions set by the clients.